Elimination of endemic measles transmission in Australia - Anita E Heywood; Heather F Gidding; Michaela A Riddell; Peter B McIntyre; C Raina MacIntyre; Heath A Kelly (The World Health Organization, 2009)
Elimination of endemic measles transmission is the culmination of a range of control measures at a national level. Current documentation of elimination proposed by WHO's regional offices requires achieving specific targets for surveillance process indicators. We demonstrate how Australia, although not meeting these specific targets, has satisfied multiple criteria that justify the formal declaration of measles elimination. Our review shows that few countries previously declaring measles elimination have satisfied the current WHO surveillance targets. We argue that the requirements for recognition of measles elimination should not restrict countries to a particular type of surveillance system or surveillance criteria.